(untitled) (Ghana Journal of Science, Technology and Development, 2022)
Telecommunication services have continued to evolve to meet the ever-changing bandwidth demand requirements. The electricity grid network of Ghana is faced with challenges, including low voltages, a lack of quick fault response teams, and the proximity to specific locations. Using diesel generators to address the shortfall in grid supply is expensive and has implications for greenhouse gas emissions. This study evaluated the technical and economic benefits of using a standalone solar photovoltaic (PV) system, hybrid (Solar PV/diesel), conventional diesel generators (DG), and grid extension to power an off-grid outdoor telecommunication site. Power solutions configurations were simulated using hybrid optimization of multiple electric renewables (HOMER). The study found the optimum design to be a standalone solar PV/battery system with 56.3 kW solar PV array and Sixty (60) pieces of 12 V SAGM batteries of 135 Ah. The optimum design had a net present cost (NPC) of US 88,176.00 and a cost of energy (COE) of US 0.321/kWh. The COE and the NPC of the optimum system were approximately 50% less than the design with DG only, which could significantly impact service tariff and improve access to digital connectivity. The COE from the solar PV/battery system is not competitive with the grid power supply (COE = US0.12). However, considering the electric distance limit or breakeven distance of 4.51km for grid extension, the solar PV/battery is preferred. Therefore, the stakeholders in providing power solutions to off-grid locations should consider solar PV technology.